The aggregation of silver nanoparticles in aqueous solution investigated via anodic particle coulometry. - Rees, N; Zhou, Y; Compton, R (2011)
Informative collisions: The use of quantitative oxidative collisions between silver nanoparticles (AgNPs) and an electrode surface to monitor the aggregation of single AgNPs into larger clusters is reported (see graph). Copyright © 2011 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.